PELATIHAN MARKETING PLAN BAGI PENGRAJIN SANGGAR MELATI DI KOTA BATAM - Yuanita FD Sidabutar; Angelina Eleonora Rumengan; Malahayati Rusli Bintang; Mohamad gita Indrawan; Raymond (Jurnal Pendekar Nusantara, 2023)
This community service is carried out with the aim of improving the Marketing Plan capabilities of Jasmine studio craftsmen. In this Marketing Plan Training, it will be carried out using a direct guidance method by providing material and input on obstacles faced related to marketing issues. The "training" service activities carried out have had a positive impact on society, especially craftsmen. The community service program carried out was attended by participants enthusiastically. Participants understand the importance of a Marketing Plan in running a business, participants are also able to create their own Marketing Plan.